The adolescent novel : Australian perspectives - Nimon, Maureen; Foster, John (John Elwall) (Literature and literacy for young people, 1997)
This book is a pioneering study of the modern Australian novel: defining the genre; tracing its development; explaining some of its principal features; discussing the characteristics of adolescent novels written in the past three decades; and exploring ways in which Australian adolescent novels may be seen to offer something different from works published elsewhere, to be specifically 'Australian'. Part 2 comprises essays on fifteen authors, all of whom are indisputably important in the development of the Australian adolescent novel. This book will be of interest to teacher librarians, tertiary students, teachers and senior students in high schools, children's/youth librarians, parents and all those who are interested in contemporary writing for young Australians.